2011
DOI: 10.1080/15287394.2011.582320
|View full text |Cite
|
Sign up to set email alerts
|

Assays to Determine DNA Repair Ability

Abstract: DNA repair is crucial to the integrity of the human genome since mammalian cells are continuously exposed to different chemical and physical genotoxic agents. To counteract the lesions induced by these agents, organisms have developed a number of highly conserved repair mechanisms involving numerous protein complexes grouped in several different repair pathways. The importance of studying the individual capacity to repair DNA damage lies in the observation that deficient repair mechanisms of the genome have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…The DNA repair system has been recognized as one of the most important cellular defense mechanisms responsible for the integrity of DNA. Decreased DNA repair ability is exhibited in various clinical conditions and associated with increased frequency of carcinogenesis, since unrepaired mistakes lead to an accumulation of aberrations in the genome that culminate in the genetic instability typical of many malignancies and other pathologies [ 130 ]. A limited number of previous studies were performed in order to determine the possible interference of OA with DNA repair mechanisms.…”
Section: Oa Beyond Its Role As Dsp Inductormentioning
confidence: 99%
“…The DNA repair system has been recognized as one of the most important cellular defense mechanisms responsible for the integrity of DNA. Decreased DNA repair ability is exhibited in various clinical conditions and associated with increased frequency of carcinogenesis, since unrepaired mistakes lead to an accumulation of aberrations in the genome that culminate in the genetic instability typical of many malignancies and other pathologies [ 130 ]. A limited number of previous studies were performed in order to determine the possible interference of OA with DNA repair mechanisms.…”
Section: Oa Beyond Its Role As Dsp Inductormentioning
confidence: 99%
“…DNA repair is one of the most important mechanisms to maintain genome integrity. Consequently, deficiencies in this process are often considered one of the key processes in the development of diseases such as cancer and other age-related pathologies (19). Indeed, it was previously suggested that one of the possible causes or events involved in frailty syndrome is the alteration of the cellular repair mechanisms that would result in the accumulation of genetic damage (9,10).…”
mentioning
confidence: 99%
“…The DNA repair system has been recognized as one of the most important cellular defense mechanisms responsible for the integrity of DNA. Decreased DNA repair ability is exhibited in vari-ous clinical conditions and associated with increased frequency of carcinogenesis, since inefficient repair leads to an accumulation of aberrations in the genome that culminate in the genetic instability typical of many malignancies and other pathologies (Valdiglesias et al, 2011).…”
Section: Dna Repair Abilitymentioning
confidence: 99%